Coordination between crop breeding and market intelligence: Groundnut in Tanzania - Rutsaert, Pieter; Das, Biswanath; Donovan, Jason; Train, Lila Jane (CGIAR Initiative on Market Intelligence, 2024)
This article discusses the collaboration between crop breeding and market intelligence for the development of groundnut products in Tanzania. It highlights the challenges faced in integrating social and biological sciences due to a lack of common language and unclear roles. The focus is on the creation of a Product Design Team (PDT), a multidisciplinary group that includes breeders, social scientists, industry experts, and other stakeholders to define market segments and product profiles. A key outcome from a Groundnut PDT Workshop was the identification of market requirements and information gaps to improve groundnut seed products and their value chain impact.